O tipo psicológico do inventor de religião em Aurora de Nietzsche - Seckelmann, Rafael Adalmo Silveira (2020)
The objective of this dissertation is to understand the construction, carried out by Nietzsche in Aurora, of the psychological type of the inventor of religion, a tool that Nietzsche uses to analyze the problem of the emergence of religions. Religion is an interpretation of the meaning and value of existence: it can be the expression of a healthy and strong psychological type or a psychological type that suffers from the weakening of the will, from the illness of its physiopsychological complex. The analysis of the psychological type will allow an evaluation of the values that guide religion